Three new species of the spider genus Luzonacera Li & Li, 2017 from Philippines (Araneae, Psilodercidae) - Wan-Jin Chang; Fengyuan Li; Shuqiang Li (ZooKeys, 2019)
Three new species of Luzonacera Li & Li, 2017 are described: L. francescoballarini Li & Li, sp. n. (♂♀), L. lattuensis Li & Li, sp. n. (♂♀) and L. peterjaegeri Li & Li, sp. n. (♂♀). Prior to this study, the genus was known by two species, both from Luzon Island, Philippines. So far, the genus and all five species are endemic to Luzon Island and can be found in dry or humid caves in a dark environment.